Effects of a brief action and coping planning intervention on completion of preventive exercises prescribed by a physiotherapist among people with knee pain - Koh, Li Hui; Hagger, Martin; Goh, Victor; Hart, William; Gucciardi, Daniel (Elsevier Australia, 2017)
Objectives: The present study aimed to test the efficacy of action and coping planning in promoting engagement with preventive exercises among a sample of people with knee pain. Design: Experimental trial. Methods: Individuals who presented to a physiotherapist with knee pain (N = 373, 57% female; M age = 31.54, SD = 10.06, age range = 18-69 years) completed two assessments separated by 14 days. At baseline, participants completed measures of severity of problems associated with the knee (e.g., pain, symptoms) and past behavior. Subsequently, participants were randomly assigned to an action and coping planning or control group. Two weeks later, participants retrospectively reported their preventive exercise behavior over the past 14 days. Analyses revealed that the experimental group reported a higher number of preventive exercise sessions over the 14. day period when compared with the control group. Results: Participants who planned action and coping strategies reported a greater frequency of completed preventive exercises over a 2-week period than people who did not. Conclusions: The results of this study underscore the importance of action and coping planning for the enactment of preventive exercises that are designed to manage or prevent knee pain.